Dynamic Methods for Childhood Hypoglycemia Phenotyping: A Narrative Review - Rossi, Alessandro; Rutten, Martijn G. S.; van Dijk, Theo H.; Bakker, Barbara M.; Reijngoud, Dirk-Jan; Oosterveer, Maaike H.; Derks, Terry G. J. (Frontiers in Endocrinology, 2022)
Hypoglycemia results from an imbalance between glucose entering the blood compartment and glucose demand, caused by a defect in the mechanisms regulating postprandial glucose homeostasis. Hypoglycemia represents one of the most common metabolic emergencies in childhood, potentially leading to serious neurologic sequelae, including death. Therefore, appropriate investigation of its specific etiology is paramount to provide adequate diagnosis, specific therapy and prevent its recurrence. In the absence of critical samples for biochemical studies, etiological assessment of children with hypoglycemia may include dynamic methods, such as in vivo functional tests, and continuous glucose monitoring. By providing detailed information on actual glucose fluxes in vivo, proof-of-concept studies have illustrated the potential (clinical) application of dynamic stable isotope techniques to define biochemical and clinical phenotypes of inherited metabolic diseases associated with hypoglycemia. According to the textbooks, individuals with glycogen storage disease type I (GSD I) display the most severe hypoglycemia/fasting intolerance. In this review, three dynamic methods are discussed which may be considered during both diagnostic work-up and monitoring of children with hypoglycemia: 1) functional in vivo tests; 2) in vivo metabolic profiling by continuous glucose monitoring (CGM); 3) stable isotope techniques. Future applications and benefits of dynamic methods in children with hypoglycemia are also discussed.